2012
DOI: 10.1124/jpet.112.191536
|View full text |Cite
|
Sign up to set email alerts
|

ABT-737 Synergizes with Bortezomib to Induce Apoptosis, Mediated by Bid Cleavage, Bax Activation, and Mitochondrial Dysfunction in an Akt-Dependent Context in Malignant Human Glioma Cell Lines

Abstract: We observed that glioma cells are differentially sensitive to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 55 publications
3
52
0
Order By: Relevance
“…Our results showed that the Combined treatment with dinaciclib and ABT-737 induced the loss of mitochondrial membrane potential, activated the mitochondrial pathway of apoptosis in glioma, as evidenced by cleavage of caspase-3 and PARP (caspase-9, data not shown) and accumulation of cytosolic cytochrome c, smac/DIABLO, apoptosis-inducing factor, and activation of Bax. The activation of Bax, including Bax conformational changes and oligomerization, appears to play a crucial role in the initiation of dinaciclib-and ABT-737-induced apoptosis, consistent with our observation that the activation of Bax, including Bax conformational changes and oligomerization, appears to play an important role in the initiation of apoptosis after targeted therapies in gliomas (Premkumar et al, 2012;Foster et al, 2014). Annis et al (2005) presented evidence that Bax inserts into the mitochondrial outer membrane as a monomer and then undergoes a conformational change and homooligomerization to form pores.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Our results showed that the Combined treatment with dinaciclib and ABT-737 induced the loss of mitochondrial membrane potential, activated the mitochondrial pathway of apoptosis in glioma, as evidenced by cleavage of caspase-3 and PARP (caspase-9, data not shown) and accumulation of cytosolic cytochrome c, smac/DIABLO, apoptosis-inducing factor, and activation of Bax. The activation of Bax, including Bax conformational changes and oligomerization, appears to play a crucial role in the initiation of dinaciclib-and ABT-737-induced apoptosis, consistent with our observation that the activation of Bax, including Bax conformational changes and oligomerization, appears to play an important role in the initiation of apoptosis after targeted therapies in gliomas (Premkumar et al, 2012;Foster et al, 2014). Annis et al (2005) presented evidence that Bax inserts into the mitochondrial outer membrane as a monomer and then undergoes a conformational change and homooligomerization to form pores.…”
Section: Discussionsupporting
confidence: 78%
“…have demonstrated that malignant human glioma cells are resistant to ABT-737, with an IC50 around 30-50 mM after 24 hours of exposure (Premkumar et al, 2012). Interestingly, as shown in Fig.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…As a single agent ABT-737, a novel Bcl -2/ Bcl -xL inhibitor triggers apoptosis in various types of human cancers including multiple myeloma, leukemia, lymphoma and small cell lung cancer. [25][26][27][28][29] However, we [30][31][32] and others 33 have demonstrated that ABT-737 minimally inhibits cell growth in glioma when used as a single agent. The complexity of the interactions between cell surface receptors and downstream signaling targets has called into question the clinical utility of blocking any target in isolation, and the results of single agent-based strategies have to date been disappointing in patients with glioma.…”
Section: Introductionmentioning
confidence: 99%